Analysis of digital interfaces data transmission in communication channels of computer systems - Dovhij, V.V.; Terletsky, A.I.; Hryha, V.M.; Svyd, I.V. (Radiotekhnika, 2024)
This work demonstrates that digital data transmission interfaces in communication channels of computer systems directly affect the speed and quality of data transmission. It provides an overview and analysis of the main encoding methods for synchronous and asynchronous data transmission, along with an example of encoding two bits of information using a quadrature-phase modulator. The text encoding system (IRA) and the American Standard Code for Information Interchange (ASCII) are analyzed. The main methods of data transmission in synchronous and asynchronous modes are reviewed, and their key characteristics, advantages, and disadvantages when used in data transmission interfaces in computer systems are identified. This article examines two of the most important interface types: V.24/EIA-232F and ISDN. This is demonstrated through an analysis of an information transmission system, with a detailed description of the equipment that can be used under specific conditions and requirements. The article also provides details on the use of different network configurations. The main principles of programming modems and multiplexers for digital information transmission using a digital communication channel for defined usage scenarios are also presented.